On the fringes of the harmonious society Tibetans and Uyghurs in socialist China - Brox, Trine; Beller-Hann, Ildiko (NIAS studies in Asian topics,, 2014)
Explores how the PRC's 'carrot and stick' approach to its two most problematic nationalities, the Tibetans and Uyghurs, has been implemented and reacted to in the economy, education, popular culture, religious policies and other arenas.